Adult Crying - Majluf, Alegría (1998)
The results of a first cross-cultural study on adult crying in 30 countries including Peru are presented. Vingerhoets et al. (1997) from the University of Tilburg have analyzed motives, tendencies and frequency of crying, emotions and feelings that provoke crying, as well as differences and similarities among countries and sexes. Results show that women have a tendency to cry more frequently and intensively than men. It has also been noted that, in certain countries, there is a link between crying in women and their monthly period.